Engineering a Microbial Consortium Based Whole-Cell System for Efficient Production of Glutarate From L-Lysine - Wang, Xin; Su, Rui; Chen, Kequan; Xu, Sheng; Feng, Jiao; Ouyang, Pingkai (Frontiers in Microbiology, 2019)
Glutarate is an important C5 platform chemical produced during the catabolism of L-lysine through 5-aminovalerate (5-AMV) pathway. Here we first established a whole-cell biocatalysis system for the glutarate production from L-lysine with the engineered Escherichia coli (E. coli) that co-expressed DavAB and GabDT. However, the accumulation of intermediate 5-aminovalerate was identified as one important factor limiting glutarate production. Meanwhile, the negative interaction of co-expressing DavAB and GabDT in a single cell was also confirmed. Here we solved these problems through engineering a microbial consortium composed of two engineered E. coli strains, BL21-22AB and BL21-YDT, as the whole-cell biocatalysts, each of which contains a part of the glutarate pathway. After the optimization of bioconversion conditions, including temperature, metal ion additives, pH and cell ratio, 17.2 g/L glutarate was obtained from 20 g/L L-lysine with a yield of 95.1%, which was improved by 19.2% compared with that in a single cell. Little accumulation of 5-aminovalerate was detected. Even at the high substrate concentration, the reduced 5-aminovalerate accumulation and increased glutarate production were achieved. This synthetic consortium produced 43.8 g/L glutarate via a fed-batch strategy, the highest titer reported to date.